The Influence of The Structural Analytic Synthetic Methods on The Early Reading Ability of Children In Kindergarten-B-Age in Sabilul Huda Kaloran Islamic Kindergarten - Esti Handayani, Diana; Tasuah, Neneng (BELIA: Early Childhood Education Papers, 2021)
This study aims to determine the effect of the Structural Analytic Synthetic method on the early reading ability in kindergarten-B-age children. The research approach used is a quantitative approach to the type of experimental approach. The research design used is research design from pre-experimental design is a one-group pretest-posttest design. The subjects in this study were kindergartners B in Sabilul Huda Kaloran Islamic Kindergarten, totaling 35 children. The data collection technique used is to scale the aspects of the development of early reading skills in kindergarten-B-age children with a total of 34 valid items that have previously been tested, so that they can be used in research. The data analysis techniques used in this study were descriptive statistical data analysis and hypothesis testing using paired sample t-test. All calculations were processed using IBM SPSS 20. Early reading ability of children in kindergarten-B-age before being given treatment in the very low category reached 14.5%, the low category reached 40%, the high category reached 45.7% and the very high category reached 0%. Whereas after being given treatment in the very low category reached 0%, the low category reached 5.7%, the high category reached 68.6% and the very high category reached 25.7%. This shows that there is an increase in the percentage of early reading skills in kindergarten-B-age children before and after treatment. Based on paired sample t-test calculation, it is known that the tcount = -16.002> ttable = 1.673 so that Ho is rejected and Ha is accepted, in other words, there are differences in the average pretest and posttest results, which means that there is an influence of structural analytic synthetic methods on the early reading ability of children in kindergarten-B-age in Sabilul Huda Kaloran Islamic Kindergarten.